FUNCTIONAL SEMANTIC FEATURES OF TOURISM TERMS (SCIENCE TIME JOURNAL, 2026)
Tourism terminology represents a dynamic and interdisciplinary lexical system that reflects not only denotative meanings but also functional, cultural, and pragmatic dimensions. This study investigates the functional semantic features of tourism-related terms in English, focusing on their roles within communication, discourse, and professional contexts. Using a qualitative semantic and functional analysis, the research explores how tourism terms operate within specific communicative functions such as informative, persuasive, and service-oriented contexts. The findings demonstrate that tourism terminology is characterized by high contextual dependency, functional variability, and cultural embedding. The study contributes to the broader understanding of terminology within the linguistic picture of the world and offers insights for translation studies, intercultural communication, and tourism discourse analysis.